Global Trade and the Maritime Transport Revolution - Jacks, David S; Pendakur, Krishna (The Review of Economics and Statistics, 2010)
What is the role of transport improvements in globalization? We argue that the nineteenth century is the ideal testing ground for this question: freight rates fell on average by 50% while global trade increased 400% from 1870 to 1913. We estimate the first indices of bilateral freight rates for the period and directly incorporate these into a standard gravity model. We also take the endogeneity of bilateral trade and freight rates seriously and propose an instrumental variables approach. The results are striking as we find no evidence that the maritime transport revolution was the primary driver of the late nineteenth century global trade boom. Rather, the most powerful forces driving the boom were those of income growth and convergence.